(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Water quality is an important issue in ground water studies and is just as important as its quantity owing to the fitting of water for various purposes. The main objectives of this study are to determine the chemical and physical characteristics of ground water of Ainsifni Pila Spi aquifer and to asses its quality for determining its suitability for domestics and irrigation purpose and to compare the concentration of both cations and anions with that of WHO. Ground water samples were collected from 8 drilling wells, during field work in Sept. 2014, for the analysis of their chemical composition of major cations and anions. The analysis comprises physical and chemical parameters of ground water such as; EC, pH, TDS, Na, K, Ca, Mg. HCO3, CO3, SO4, CL and NO3. Chemical parameters such as, total hardness (TH), sodium percent (Na%) and sodium adsorption ratio (SAR), were calculated, based on the analytical results of ground water samples. Basement rocks of the studied area which is crop out at the surface of ainsifni anticline, are represented by Pila Spi Formation of Middle Miocene age which consist of limestone. It is overlain by Quaternary sediments which are highly permeable beds. Hydrochemical analysis are analyzed graphically using Piper diagram to determine the suitability and type of the groundwater. Sodium adsorption ratio (SAR) and sodium percentage (Na%) are also calculated to show the suitability of ground water for agricultural irrigation. According to the results of chemical analysis of ground water samples, types of water are of CaHCO3 and mix Ca-Mg-HCO3. More over ground water samples are of moderate TDS which is within the specification of (TDS) values set up by the WHO, medium TH and generally groundwater of the studied are is of alkalinity in nature. The over all quality of ground water samples of the studied area in most chemical constituents is on the moderate side in comparing with that of WHO due to its unique location away from any behavior of environmental pollutants. Rainfall water is the only source of replenishment to the groundwater aquifer.